THE EFFECT OF FINANCIAL LITERACY ON THE INCOME OF CULINARY SMES IN TANA TORAJA REGENCY THROUGH PERFORMANCE - Golda, Cipta; Todingbua, Manuel A; Halik, Johannes Baptista (Indonesian Journal Of Economy Studies, 2024)
According to the Tana Toraja Central Statistics Agency, the number of culinary SMEs in Tana Toraja Regency continues to grow, in line with increasing economic activity in the area. However, this growth has not been accompanied by optimal financial management by business actors. One of the main obstacles for SMEs is low financial literacy. The aim of this research is to find out how financial literacy influences income through the performance of culinary SMEs in Tana Toraja Regency. This research uses a quantitative method with a sample size of 96 obtained using a purposive sampling technique. Hypothesis testing was carried out by analyzing the path coefficient and the results obtained showed that financial literacy had an influence on income through performance. However, Tana Toraja Regency Culinary UKM have not been able to optimally apply the knowledge they have gained through financial literacy, so suggestions are given to the district government and related parties to hold outreach and education regarding financial literacy and financial management for UKM players.Keyword: financial literacy, UKM, Income,performance